Wound hygiene survey: awareness, implementation, barriers and outcomes. (2nd July 2021) - Murphy, Chris; Atkin, Leanne; Hurlow, Jenny; Swanson, Terry; de Ceniga, Melina Vega
Abstract : Objective: In light of the COVID-19 pandemic, which has resulted in changes to caseload management, access to training and education, and other additional pressures, a survey was developed to understand current awareness and implementation of the wound hygiene concept into practice one year on from its dissemination. Barriers to implementation and outcomes were also surveyed. Method: The 26-question survey, a mixture of multiple choice and free-text, was developed by the Journal of Wound Care projects team, in consultation with ConvaTec, and distributed globally via email and online; the survey was open for just over 12 weeks. Due to the exploratory nature of the research, non-probability sampling was used. The authors reviewed the outputs of the survey to draw conclusions from the data, with the support of a medical writer. Results: There were 1478 respondents who agreed to the use of their anonymised aggregated data. Nearly 90% were from the US or UK, and the majority worked in wound care specialist roles, equally distributed between community and acute care settings; 66.6% had been in wound care for more than 8 years. The respondents work across the spectrum of wound types. More than half (57.4%) had heard of the concept of wound hygiene, of whom 75.3% have implemented it; 78.7% answered that they 'always' apply wound hygiene and 20.8% 'sometimes' do so. The top three barriers to adoption were confidence (39.0%), the desire for more research (25.7%) and competence (24.8%). Overall, following implementation of wound hygiene, 80.3% reported that their patients' healing rates had improved. Conclusion: Respondents strongly agreed that implementing wound hygiene is a successful approach for biofilm management and a critical component for improving wound healing rates in hard-to-heal wounds. However, the barriers to its uptake and implementation demonstrate that comprehensive education and training, institutional support for policy and protocol changes, and more clinical research are needed to support wound hygiene.